Economic evaluation of cervical cancer screening strategies in urban China - Ma, Li (Chin J Cancer Res, 2019)
OBJECTIVE: This study evaluated the feasibility of different cervical cancer screening strategies in urban China. METHODS: A Markov model was constructed to simulate a hypothetical cohort of 100,000 females aged 30−59 years in a 20-year period. Screening strategies included liquid-based cytology (LBC) every three years, human papillomavirus (HPV) DNA testing every three and five years, respectively, and a combination of HPV DNA testing and LBC (HPV+LBC) every three and five years, respectively. Model outcomes included cumulative incidence over 20 years, cumulative risk of cervical cancer, costs, life year saved (LYS), quality-adjusted life years (QALYs) and benefits. The cost-effectiveness ratios (CERs), incremental cost-effectiveness ratios (ICERs), cost-utility ratios (CURs), and benefit-cost ratios (BCRs) were used as outcomes in the health economic evaluation analysis. Univariate sensitivity analyses were performed to examine the stability of the results. RESULTS: The cumulative incidence of the five screening strategies ranged from 833.02 to 1,158.07 cases per 100,000 females. HPV DNA testing was most effective in reducing the cumulative risk of cervical cancer, saving life years and QALYs and gaining benefits. The CERs of HPV DNA testing every three and five years, and LBC every three years were considered to be very cost-effective if they were below China’s GDP per capita. The CERs of HPV+LBC were considered to be cost-effective if they were below three times GDP per capita. The incremental cost-effectiveness analysis showed that HPV DNA testing every three and five years, LBC every three years and HPV+LBC every five years were dominant strategies. CONCLUSIONS: The findings of this study indicated that HPV DNA testing every five years or LBC every three years should be recommended in urban China.